Prevalence of the erm(T) Gene in Clinical Isolates of Erythromycin-Resistant Group D Streptococcus and Enterococcus - DiPersio, Linda P. (American Society for Microbiology (ASM), 2008)
Among 48 erythromycin-resistant group D streptococci (GDS), 36 had the erm(T) resistance gene. erm(T) was also found in 4 of 31 erythromycin-resistant Enterococcus faecium isolates. This is the first report of the erm(T) gene in U.S. GDS isolates and the first report of the erm(T) gene in enterococci.